Endometrial factors in the implantation failure spectrum: protocol of a MUltidisciplinary observational cohort study in women with Repeated Implantation failure and recurrent Miscarriage (MURIM Study). Issue 6 (8th June 2022) - Stevens Brentjens, Linda; Habets, Denise; Den Hartog, Janneke; Al-Nasiry, Salwan; Wieten, Lotte; Morré, Servaas; Van Montfoort, Aafke; Romano, Andrea; van Golde, Ron
Abstract : Introduction: Women with repeated implantation failure (RIF) and unexplained recurrent miscarriage (RM) are proposed to be at opposite ends of the implantation spectrum, with RM representing an overly receptive endometrium (implantation of genetically aberrant or poor-quality embryos) versus RIF representing an overly selective endometrium (no implantation even with good quality embryos). In both cases, often no explanation for reproductive failure can be found and although promising add-on treatments have been introduced, therapeutic options are frequently limited to supportive care. Both RM and RIF are multifactorial and research indicates that the interplay between steroidogenesis, uterine natural killer (uNK) cells and the microbiome determine the capacity of the endometrium to be a biosensor for invading embryos. Our objective is to elucidate whether there is a difference in endometrial receptivity parameters (ie, steroid metabolism, uNK cells and the microbiome) between women aged 18–38 years with reproductive failure (RIF and RM), and fertile controls. Methods and analysis: Single-centre, observational cohort study. Endometrial biopsies, vaginal swabs and peripheral blood will be collected during the window of implantation and menstrual blood in the subsequent menstruation. The study parameters are the steroid profile (steroid levels and mRNA levels, protein expression and activity of steroid enzymes) in endometrial tissue and peripheral blood, as well as the activating or inhibitory phenotype of uNK cells based on receptor expression in menstrual blood and endometrial tissue and determination of the vaginal and endometrial microbiome using the inter spacer bacterial profiling technique. Ethics and dissemination: The protocol is approved by the local medical ethical review committee at the Maastricht University Medical Centre. Findings from this study will be shared with the academic and medical community and the patient organisations to optimise and individualise medical care of patients with implantation failure and miscarriages. Trial registration number: NTR7571, registered 28 February 2019.